Ergonomics in Dermatologic Surgery: Lessons Learned Across Related Specialties and Opportunities for Improvement. Issue 6 (June 2020) - Chan, Justin; Kim, Dong Joo; Kassira-Carley, Sama; Rotunda, Adam M.; Lee, Patrick K.
Abstract : BACKGROUND: As the practice of dermatology becomes increasingly procedurally based, there is a concordant rise in musculoskeletal injury (MSI) risk. Dermatologic surgeons are most susceptible and, although the majority suffer from MSI, few have received any formal ergonomics training. This stems from a lack of awareness of this troubling trend and a paucity of research and education on the ergonomics of dermatologic surgery. OBJECTIVE: To highlight pertinent ergonomics principles and strategies from other specialties that could be translated into dermatology, and to synthesize general recommendations aimed at reducing MSI among dermatologic surgeons. MATERIALS AND METHODS: A comprehensive search of the PubMed and Cochrane Reviews databases from 1975 to 2019 was conducted, using a combination of ergonomics-related search terms, generating 6 publications from the dermatology literature and 58 from the fields of dentistry, medicine, and select surgical subspecialties. RESULTS: This multidisciplinary approach yielded multiple interventions that could be applied directly (i.e., adequate lighting, adjustable operating tables, and surgical seat heights) or indirectly pending further investigation into their feasibility (i.e., video displays of the surgical field to allow neutral head and neck postures). CONCLUSION: Although much can be learned from decades of prior ergonomics research from other specialties, considerations that are unique to dermatology remain and must be addressed with specialty-specific research.